Hairy cell leukemia: a rare case report - Sapre, Jyoti P.; Joshi, Hetal J.; Shah, Menka H.; Shah, Ronak D. (International Journal of Research in Medical Sciences, 2017)
Hairy cell leukemia (HCL) is a rare chronic B-cell leukemia accounting for 2% of all the leukemias and occurs more frequently in the elderly males. The etiology is unknown but possible relationships to radiation exposure, exposure to benzene, to farm animals and to commercial herbicides and pesticides have been identified. Familial predisposition among first degree relatives has been noted. It is characterized by distinctive cytoplasmic “hair like” projections on the cell surface of lymphoid cells, pancytopenia and splenomegaly. We report a rare case of 29 year old female, farm labourer presenting with fever, fatigue and weakness for 1 month. On examination the patient had hepatomegaly, massive splenomegaly and inguinal lymphadenopathy. After peripheral smear examination diagnosis of HCL was made which was confirmed by bone marrow aspiration examination, bone marrow biopsy and immunohistochemistry (IHC).